The significance of clean audits on the provision of electricity in South African local municipalities - Manyathi, Sakhile (University of the Witwatersrand, Johannesburg, 2024)
The South African Constitution specifies the various responsibilities of local governments. Responsibilities include providing their respective jurisdictions with reliable basic municipal services (Constitution, 1996: 74). Municipalities must abide by specific municipal and procurement legislation while providing basic municipal services. Local and metropolitan municipalities were chosen to be part of this study as they are mandated to ensure quality electrical grid connection, which is the main focus of this study. Electricity connection for citizens was chosen as a measure of service delivery because all local and metropolitan municipalities have this competency. The main aim of this study was to determine whether a relationship exists between clean audits and improved service delivery, specifically new electricity connections, in local municipalities, and service delivery was measured in new connections to the national electricity grid. According to the analysis of the previous studies, none of them found a connection between clean audit opinions and improved service delivery, confirming the gap and research niche for the current study. The study applied a quantitative approach using secondary data sourced from Stats SA and AGSA. This is mainly because the quantitative approach enables the study to consider statistical data to quantify service delivery performance measurements: residents' electricity connections to the grid together with clean audits. The results suggest that electricity provisions in these municipalities are most likely to be explained by other variables that were not part of the current study. Overall, according to the analysis conducted in the current study, the researcher cannot rule out the possibility that clean audits have no effect on electricity provision. Therefore, the Null Hypothesis (H0), which states that there is no relationship between the achievement of clean audits and an improvement in the provision of municipal electricity, cannot be rejected.
A research report submitted in fulfillment of the requirements for the Master of Management, In the Faculty of Faculty of Commerce, Law and Management, Wits School of Governance, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Local and metropolitan municipalities; service delivery; clean audits; electricity; public governance; relationships; SDG-8: Decent work and economic growth